High-sensitivity Paper-based Capacitive Humidity Sensors for Respiratory Monitoring - Song, Z.; Li, S.Q.; Hou, B.J.; Cheng, Z. H.; Xue, Y.B.; Chen, B.J. (IEEE sensors journal, 2023)
Paper-based humidity sensors have attracted considerable research attention owing to their low cost, flexibility, and biodegradability. The problem of current paper-based humidity sensors is that they cannot simultaneously satisfy high sensitivity and fast response/recovery speed. To solve this problem, this paper presents a new type of paper-based capacitive humidity sensor. The sensor comprises interdigitated electrodes (IDE) and graphene oxide (GO) as the moisture-sensitive material. A sensing model with better performance was obtained by optimizing the IDE structure. The effect of different types of paper substrates on the performance of the sensor was investigated systematically, and an approach for selecting paper substrates in sensor design was formulated. The performance of the sensor was further improved by optimizing the parameters of the sensitive GO film and the operating frequency. Results show that the sensor achieves ultrahigh sensitivity to humidity (maximum of 32,146%) at an operating frequency of 100 Hz and combines high sensitivity (8504%) with fast response/recovery time (170/40 s) at an operating voltage of 500 Hz. Further, the results of preliminary respiratory-monitoring experiments show that the proposed sensor exhibits excellent reliability in respiratory monitoring. It can accurately record the respiratory rate and respiratory depth of the subject in each breathing pattern. A portable respiratory-monitoring system was fabricated, which confirmed the excellent respiratory-monitoring performance and practical potential of the proposed sensor.